Consumer‐resource stoichiometry as a predictor of trophic discrimination (Δ13C, Δ15N) in aquatic invertebrates. (29th June 2018) - Brauns, Mario; Boëchat, Iola G.; de Carvalho, Ana Paula C.; Graeber, Daniel; Gücker, Björn; Mehner, Thomas; von Schiller, Daniel
Abstract: Trophic interactions are important pathways of energy and matter fluxes in food webs and are commonly quantified using stable isotopes of carbon (δ 13 C) and nitrogen (δ 15 N). An important prerequisite for this approach is knowledge on the isotopic difference between consumer and resource (trophic discrimination, Δ 13 C and Δ 15 N). The range and mechanism causing variation of trophic discrimination factors remain unclear. We conducted a controlled feeding experiment with 13 freshwater benthic invertebrate taxa fed with six resources to test if the C:N, C:P and N:P ratios of consumer, resources and consumer‐resource imbalances are significant predictors of Δ 13 C and Δ 15 N. We compiled the available literature on discrimination factors for aquatic invertebrates from controlled feeding experiments and field studies to compare the variation in trophic discrimination. Molar C:N and C:P ratios of resources as well as consumer‐resource imbalances of C:N were significantly related to Δ 13 C and explained more than 40% of variation of Δ 13 C, respectively. Resource %N was unrelated to Δ 15 N, but consumer N:P explained 20% of variation of Δ 15 N. Our data taken together with the literature compilation provide a mean Δ 13 C of 0.1‰ ( SD  = 2.2, N  = 157) and a mean Δ 15 N of 2.6‰ ( SD  = 2.0, N  = 155) for aquatic invertebrates to be used in mixing model analysis for estimating dietary proportions. Our study bridges the currently separated disciplines of stable isotope discrimination and ecological stoichiometry and shows that resource C:N:P and consumer‐resource imbalances are powerful predictors of invertebrate trophic discrimination. Including these stoichiometric predictors into stable isotope mixing models may improve the estimates of the contribution of organic matter sources to the diet of invertebrate consumers. The overall discrimination factors for aquatic invertebrates derived from this study may help to produce precise estimates in trophic ecology if taxon‐specific discrimination factors are unavailable.